2015
DOI: 10.1590/1519-6984.02814
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antioxidant activities of Enterococcus species isolated from meat and dairy products

Abstract: Lactic acid bacteria (LAB) have an important role in a great variety of fermented foods. In addition to their contribution to sensory characteristics, they enhance food preservation and can be used as probiotics. In this study, the antimicrobial and antioxidant activities of culture supernatants and cell free extracts of 16 LAB isolated from meat and dairy products were investigated. The bacterial were identified by 16S rRNA sequencing. GenBank BLAST analysis revealed that all the isolates belong to Enterococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…a Proteolytic activity, diacetyl production, titratable acidity (% acid) and pH variation (Δ pH); b antioxidant activity of the supernatant (AAS), antioxidant activity of the intracellular extract (AAIE), resistance to intestinal juice with (RIJ+) and with no addition of bile salts (RIJ-), resistance to gastric juice (RGJ) at two pH values (2.5 and 3.0), proteolytic activity and diacetyl production; and c Intensity of the resistance to 12 antibiotics -0.8 -0.4 0.4 1. (Pieniz et al 2015). The antioxidant potential observed in the lactobacilli studied in this work suggests that they may be useful for the development of functional foods acting as antioxidants to eliminate free radicals from host cells.…”
Section: Discussionmentioning
confidence: 74%
“…a Proteolytic activity, diacetyl production, titratable acidity (% acid) and pH variation (Δ pH); b antioxidant activity of the supernatant (AAS), antioxidant activity of the intracellular extract (AAIE), resistance to intestinal juice with (RIJ+) and with no addition of bile salts (RIJ-), resistance to gastric juice (RGJ) at two pH values (2.5 and 3.0), proteolytic activity and diacetyl production; and c Intensity of the resistance to 12 antibiotics -0.8 -0.4 0.4 1. (Pieniz et al 2015). The antioxidant potential observed in the lactobacilli studied in this work suggests that they may be useful for the development of functional foods acting as antioxidants to eliminate free radicals from host cells.…”
Section: Discussionmentioning
confidence: 74%
“…Enterococci are important Gram-positive bacteria recognized as part of gut microbiota in humans and animals, and they are widely distributed in soil, water, plants and foods (Cassenego et al, 2013;Lebreton et al, 2014;Pieniz et al, 2015;Santestevan et al, 2015;Prichula et al, 2016;Medeiros et al, 2017). Their ubiquity reflects its ability to survive in a variety of environmental stressors (Byappanahalli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, reactive oxygen species such as hydroxyl radicals (•OH), superoxide anions (•O 2 − ), and hydrogen peroxide are produced during the process (Choi and others ). An oxidative stress process can damage biomolecules, including proteins, lipids, and nucleic acids, when reactive oxygen species are generated as a result of excess or deficient cellular defenses (Pieniz and others ). This damage may result in a variety of degenerative diseases such as cancer, atherosclerosis, and cirrhosis (Pieniz and others ).…”
Section: Introductionmentioning
confidence: 99%
“…An oxidative stress process can damage biomolecules, including proteins, lipids, and nucleic acids, when reactive oxygen species are generated as a result of excess or deficient cellular defenses (Pieniz and others ). This damage may result in a variety of degenerative diseases such as cancer, atherosclerosis, and cirrhosis (Pieniz and others ). Studies have shown that LAB isolates have the scavenging capacities of free radicals such as 1,1‐diphenyl‐2‐picrylhydrazyl free radical (DPPH•), OH•, and O 2 − • (Chen and others ; Ji and others ).…”
Section: Introductionmentioning
confidence: 99%